Water disinfection processes change the cytotoxicity of C60 fullerene: Reactions at the nano-bio interface. (15th October 2019) - Zhang, Qiurong; Wang, Meiling; Gu, Chuanhui; Zhang, Chengdong
Abstract: The environmental transformation of nanoparticles results in significant changes in their structure, properties, and toxicity, which are imperative for assessing their environmental impact and health risks. Little is known about the toxicity alteration of fullerene nanoparticles (C60 ) after water disinfection processes considering their potential application in antimicrobial control in water treatment ultimately ending in sewage treatment plants. We showed that C60 aggregates ( n C60 ) were converted to more oxidized forms via commonly used water disinfection processes (i.e., phototransformation and photochlorination treatment). The light-irradiated nanoparticles (UV_ n C60 ) exhibited mitigated cytotoxicity relative to n C60, whereas photochlorinated n C60 (UV/Cl_ n C60 ) showed an exacerbated outcome. We revealed a distinct toxic mechanism occurring at the nano-bio interface, for which electrons were shuttled by C60 nanoparticles from membrane-bound NADPH oxidase to extracellular molecular oxygen, resulting in the production of various extracellular reactive oxygen species (ROS). UV/Cl_ n C60 showed the highest electron-shuttling activity due to its high carbonyl content, and more than 2.4-fold higher level of extracellular hydroxyl radicals were detected relative to that in untreated cells. Although UV_ n C60 possessed a somewhat higher carbonyl content than n C60, it showed a weaker adhesion to the cell membrane, which compromised the electron-transfer process. The intrinsic ROS generation/quenching capabilities and oxidative potentials of the various nanoparticles were also systematically compared. Overall, this report highlights the importance of understanding environmental transformations in risk assessment and uncovers an overlooked mechanism through which n C60 /derivatives can modulate the electron transfer process at the nano-bio interface via acting as electron shuttles. Graphical abstract: Image 1 Highlights: Water disinfection processes change the structures of C60 nanoparticles. UV-irradiated C60 showed less cytotoxicity relative to pristine C60 . Photochlorinated C60 exacerbated the toxic effect. C60 nanoparticles acted as electron mediators at the nano-bio interface. Electron-shuttling activity was dependent on the structural carbonyl content.